Revisiting Classical Methods to Identify Collapsible Soils - Vilar, O. M.; Rodrigues, R. A. [UNESP] (Brazilian Soc Soil Mechanics & Geotechnical Engineering, 2015)
The paper revisits and updates two expedite methods used to identify the occurrence of collapsible soils. The methods were proposed by Gibbs (1961) and de Mello (1973) and have in common the assumption that collapsible soils are usually low density soils characterized through the relative compaction at natural condition, ratio between in situ dry-density and maximum dry density from Standard Proctor compaction test. The method by Gibbs (1961) considers in addition the soils moisture deviation, the difference between in situ moisture content and optimum moisture content. Data from different origin soils of all over the world were used and analyzed and equations were proposed to separate collapsible and non-collapsible soils. The updated procedures, as the original ones, were intended for use during preliminary investigation to identify potentially collapsible soil and to serve as a basis for planning more precise methods of investigation.
Keywords: collapsible soils; identification; unsaturated soil